Clinical Features of Chronic Spontaneous Urticaria that Predict Disease Prognosis and Refractoriness to Standard Treatment - Laia Curto-Barredo; Laura Riba Archilla; Guillem Roura Vives; Ramon M. Pujol; Ana M. Giménez-Arnau (Medical Journals Sweden, 2018)
Chronic spontaneous urticaria (CSU) is characterized by heterogeneous activity, evolution, associated comorbidities and response to treatment. The aim of this study was to identify prognostic factors in patients with CSU that predict disease course and response to standard treatments. An observational retrospective study was conducted in a cohort of 549 patients with CSU, comparing patients with isolated CSU and those with CSU with concomitant inducible urticaria (CSU-CIndU). The factors associated with a worse prognosis in terms of duration and/or CSU activity and its episodes were: multiple episodes of CSU (19.2% had more than one lifetime episode of CSU), late-onset (63.6% of patients developed first onset of CSU after the age of 45 years), concomitant CIndU (20.2%) and functional serum autoreactivity. Patients with CSU-CIndU required more frequent therapy after 5 years and higher doses of 2nd-generation H1-antihistamines. Of patients with a baseline Urticaria Activity Score 7 (UAS7) between 16 and 42, 84.6% required cyclosporine or omalizumab to achieve symptom control, compared with 15.4% of patients with a baseline UAS7 between 0 and 15 (p?=?0.0013). Baseline CSU activity is the only factor found to be predictive for refractoriness to treatment with H1-antihistamines.